E-BILLING SYSTEM, E-FILING, TAPPING BOX, TAX SANCTIONS AGAINST TAXPAYER COMPLIANCE WITH TAX UNDERSTANDING AS A MODERATING VARIABLE - Oktavia Rita Panda Wangi; Herman Ernandi (Antis Publisher, 2025)
Objective: This study aims to analyze the effect of the implementation of e-billing, e-filing, tapping box, and tax sanctions on taxpayer compliance, with tax understanding as a moderating variable. Method: The population in this study includes all taxpayers of Pia MSMEs in Gempol District, Pasuruan. Primary data were collected by distributing questionnaires to taxpayers. The sample was selected using a purposive sampling technique based on certain criteria, resulting in 41 taxpayers being selected as research samples. The data were analyzed using the Multiple Linear Regression Analysis method with the help of SPSS 25 software. Result: The results of the study indicate that e-billing, e-filing, tapping box, and tax sanctions have an effect on taxpayer compliance, and tax understanding is able to moderate the effect of e-billing, e-filing, tapping box, and tax sanctions on taxpayer compliance. Novelty: This study provides new insights into the role of tax understanding as a moderating variable, showing its influence on the relationship between electronic tax systems and taxpayer compliance, a perspective that has not been fully explored in previous research.